Estimasi Sumber Daya Lapisan Laterit Menggunakan Data Resistivitas di Desa Morombo Pantai Konawe Utara - Juan Gilbert; Jahidin Jahidin; Al Rubaiyn (Jurnal Rekayasa Geofisika Indonesia, 2024)
This research was conducted in Morombo Pantai Village, Langgikima District, North Konawe Regency which aims to model nickel laterite deposits in 2D and 3D to describe the distribution of nickel laterite deposits in the subsurface based on resistivity values. The inversion process uses Res2DInv software to produce 2D ERT cross-sections and the distribution of resistivity values that provide an overview of the lithology in the subsurface. These results were then correlated with local coordinates and modeled in 3D using Rockworks17 software. The results show the distribution of laterite deposits with thicknesses ranging from 1.63 m to 59 m that spread from north to south. Based on the 3D modeling results, it is known that the resource of nickel laterite deposits at the research site reaches 2,931,836.0 m3 for the limonite layer and 3,820,284.0 m3 for the saprolite layer